2014
DOI: 10.1016/j.molbiopara.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum aldolase and the C-terminal cytoplasmic domain of certain apical organellar proteins promote actin polymerization

Abstract: The current model of Apicomplexan motility and host cell invasion is that both processes are driven by an actomyosin motor located beneath the plasma membrane, with the force transduced to the outside of the cell via coupling through aldolase and the cytoplasmic tail domains (CTDs) of certain type 1 membrane proteins. In Plasmodium falciparum (Pf), aldolase is thought to bind to the CTD of members of the thrombospondin-related anonymous protein (TRAP) family, which are micronemal proteins and represented by MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 43 publications
0
20
1
Order By: Relevance
“…In this scenario, actin/motor-mediated displacement/capping of MTRAP along the PPM might lead to the disruption of the PVM. Several lines of indirect evidence fit in well with this hypothesis: (1) surface localization of MTRAP upon gamete activation; (2) a ribbed MTRAP staining pattern seen in mature gametocytes (Figure S6) reminiscent of that seen with GAP50 (Dixon et al., 2012), suggesting that MTRAP might also be, like other members of the TRAP family of proteins, a glideosome-associated protein; (3) patchy distribution of surface-associated MTRAP after activation, suggesting that MTRAP aggregation in the membrane might be part of the activation process; and (4) the recent demonstration, in line with our cytochalasin and jasplakinolide inhibition experiments, that the MTRAP cytoplasmic tail is sufficient to stimulate actin polymerization in vitro (Diaz et al., 2014). Of note, the conformation of recombinant MTRAP (rMTRAP) appears to be a highly extended linear, rod-like protein (2 nm by 33 nm, width by length, respectively) (Uchime et al., 2012), which is in agreement with a putative role of MTRAP in bridging the PPM and PVM.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In this scenario, actin/motor-mediated displacement/capping of MTRAP along the PPM might lead to the disruption of the PVM. Several lines of indirect evidence fit in well with this hypothesis: (1) surface localization of MTRAP upon gamete activation; (2) a ribbed MTRAP staining pattern seen in mature gametocytes (Figure S6) reminiscent of that seen with GAP50 (Dixon et al., 2012), suggesting that MTRAP might also be, like other members of the TRAP family of proteins, a glideosome-associated protein; (3) patchy distribution of surface-associated MTRAP after activation, suggesting that MTRAP aggregation in the membrane might be part of the activation process; and (4) the recent demonstration, in line with our cytochalasin and jasplakinolide inhibition experiments, that the MTRAP cytoplasmic tail is sufficient to stimulate actin polymerization in vitro (Diaz et al., 2014). Of note, the conformation of recombinant MTRAP (rMTRAP) appears to be a highly extended linear, rod-like protein (2 nm by 33 nm, width by length, respectively) (Uchime et al., 2012), which is in agreement with a putative role of MTRAP in bridging the PPM and PVM.…”
Section: Discussionmentioning
confidence: 60%
“…In this interaction, two MTRAP monomers were proposed to interact via their tandem TSRs with the Sema domains of a Semaphorin-7A homodimer. More recently, the MTRAP cytoplasmic tail was shown to be sufficient to polymerize actin (Diaz et al., 2014). These data all favor a role for MTRAP during merozoite invasion of erythrocytes, possibly acting as a bridge between the motor and the erythrocyte surface.…”
Section: Introductionmentioning
confidence: 99%
“…Parasite aldolase, an actin-binding protein involved in parasite invasion and motility (Diaz et al, 2014), was found at high levels in both ring-stage and schizont-stage iRBC-EVs, whereas parasite ADF1, another actinbinding protein (Wong et al, 2014), was abundant in iRBC-EVs from the schizont stage ( Figure 1b). SR1 is an RBC protein and known marker of erythrocyte-derived vesicles (Salzer, Hinterdorfer, Hunger, Borken, & Prohaska, 2002) and was used to demonstrate equivalent loading of all samples.…”
Section: Extracellular Vesicles From Early Stage Irbc Contain the Vmentioning
confidence: 99%
“…It is known that the Cterminal part responsible for alignment and attachment of substrates during catalysis decides the differences in activity (Hester et al 1991;Takahashi et al 1989;Diaz et al 2014). It was also proposed that, as indispensable modules in determining the characteristic properties, IGS-1 and IGS-4 regions of aldolase were required for exerting specific functions, while a Arranged in descending order by the predicted score of sjFBPA the IGS-2 and IGS-3 enhanced the catalytic activity of aldolase in collaboration with the IGS-1 and IGS-4 (Kusakabe et al 1994;Motoki et al 1993).…”
Section: Discussionmentioning
confidence: 99%